Reducing Preventable Maternal Deaths in Nepal - Thapa, Shyam (Europasian Journal of Medical Sciences, 2024)
On March 24, 2023, the Nepal Government’s National Statistics Office (formerly the Central Bureau of Statistics) and the Ministry of Health and Population (MoHP), in collaboration with several external development partners, organized a study dissemination meeting, which was attended by the then Prime Minister. The primary purpose of the event was to disseminate findings from a study that aimed at assessing the current maternal mortality status in Nepal. Unlike previous maternal mortality data obtained from probability surveys (e.g., Nepal Demographic and Health Surveys2,3), the data for this particular study were collected through a census enumeration.1 First, during the 2021 census, each household head was asked whether any deaths had occurred in the household during the 12 months preceding the census day. For any female deaths reported in the 15-49 age group, the timing of death (whether during pregnancy, delivery, post-pregnancy, or post-abortion within 42 days of delivery) was recorded. These records were then shared with the MoHP maternal mortality study team stationed in communities in the country.